Activated platelets promote an osteogenic programme and the progression of calcific aortic valve stenosis. (5th November 2018) - Bouchareb, Rihab; Boulanger, Marie-Chloé; Tastet, Lionel; Mkannez, Ghada; Nsaibia, Mohamed J; Hadji, Fayez; Dahou, Abdellaziz; Messadeq, Younes; Arsenault, Benoit J; Pibarot, Philippe; Bossé, Yohan; Marette, André; et al.
Abstract: Aims: Calcific aortic valve stenosis (CAVS) is characterized by a fibrocalcific process. Studies have shown an association between CAVS and the activation of platelets. It is believed that shear stress associated with CAVS promotes the activation of platelets. However, whether platelets actively participate to the mineralization of the aortic valve (AV) and the progression of CAVS is presently unknown. To identify the role of platelets into the pathobiology of CAVS. Methods and results: Explanted control non-mineralized and mineralized AVs were examined by scanning electron microscope (SEM) for the presence of activated platelets. In-depth functional assays were carried out with isolated human valve interstitial cells (VICs) and platelets as well as in LDLR −/− apoB 100/100 IGFII (IGFII) mice. Scanning electron microscope and immunogold markings for glycoprotein IIb/IIIa (GPIIb/IIIa) revealed the presence of platelet aggregates with fibrin in endothelium-denuded areas of CAVS. In isolated VICs, collagen-activated platelets induced an osteogenic programme. Platelet-derived adenosine diphosphate induced the release of autotaxin (ATX) by VICs. The binding of ATX to GPIIb/IIIa of platelets generated lysophosphatidic acid (LysoPA) with pro-osteogenic properties. In IGFII mice with CAVS, platelet aggregates were found at the surface of AVs. Administration of activated platelets to IGFII mice accelerated the development of CAVS by 2.1-fold, whereas a treatment with Ki16425, an antagonist of LysoPA receptors, prevented platelet-induced mineralization of the AV and the progression of CAVS. Conclusions: These findings suggest a novel role for platelets in the progression of CAVS.